Hierarchical luminescence center coupling enables time-dependent phosphorescence color from self-protective carbonized polymer dots - Meichao Shi; Qian Gao; Mingxing Chen; Ziwen Lv; Jun Rao; Gegu Chen; Baozhong Lü; Wei Qi; Junli Ren; Feng Peng (Nature Communications)
Abstract Time-dependent phosphorescence color is attractive for various applications; however, the modulation mechanism of multiple luminescence centers is still confused. Herein, we proposed a hierarchical luminescence center coupling strategy to develop self-protective xylan carbonized polymer dots with time-dependent phosphorescence color. When using 1,3-diaminopropane as the cross-linker, the polymer dots feature a highly stable and rigid architecture, the clusterization-triggered phosphorescence of which is fully exploited to form hierarchical core−shell phosphorescence centers with different afterglow colors. The core with blue afterglow is dominant at first, and the shell with yellow-green afterglow becomes dominant over time, leading to a typical time-dependent phosphorescence color evolution with large color contrast. The eco-friendly xylan carbonized polymer dots with high contrast time-dependent phosphorescence color can be used for advanced dynamic information encryption and anti-counterfeiting. This work provides an effective method to achieve time-dependent phosphorescence color, and gives insights into the phosphorescence mechanism of carbonized polymer dots.